Hand-assisted Laparoscopy: Expensive but Considerable Step Between Laparoscopic and Open Colectomy. Issue 4 (August 2018) - Gulcu, Baris; Isik, Ozgen; Ozturk, Ersin; Yilmazlar, Tuncay
Abstract : Purpose: Hand-assisted laparoscopic colectomy (HALC) and laparoscopic-assisted colectomy (LAC) have been shown to have comparable short-term outcomes while there are limited data regarding costs. The aim of our study was to compare the short-term outcomes and costs of HALC and LAC. Materials and Methods: In total, 46 patients who underwent HALC or LAC for benign or malignant disease between January 2011 and December 2014 at our institution were included in the study. Patients were randomized into HALC or LAC group. Patients' demographics and characteristics, operative details, short-term outcomes, and costs were evaluated. Results: There were 25 patients in LAC group and 21 patients in HALC group. Patient's demographics and characteristics and short-term outcomes were comparable between the LAC and HALC groups. Conversion rate was significantly lower in the HALC group (4.7% vs. 28%, P =0.03) while surgical costs (1706.83±203.70 vs. 1304.93±305.67, P =0.038) and total costs (2427.18±254.27 vs. 2044.03±215.22, P =0.021) were significantly higher in HALC group. Conclusions: HALC is associated with increased surgical and total hospital costs, and decreased rate of conversion. Although it is more expensive, HALC may be helpful by providing a step between LAC and open surgery before considering conversion.